1972
DOI: 10.1139/o72-101
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Changes in Mitochondria and Other Cellular Components of Pea Cotyledons During Germination

Abstract: Integrated studies comprising biochemical and electron microscopic analysis suggested that the increase in respiratory activity of pea cotyledon mitochondria during germination results from further development of the original mitochondria present in dormant seeds. Electron microscopy of isolated mitochondria as well as mitochondria in situ has revealed that membranes are scarce in the mitochondria present in dormant seeds. Mitochondrial cristae become well developed during the initial stages of germination. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
30
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 0 publications
6
30
0
Order By: Relevance
“…The senescence of cotyledons has also been studied (2,14,17,20,23 were soaked in tap water for 6 h. Following this, damaged and nonimbibed seeds were discarded. The remaining seeds were planted in horticultural grade Vermiculite and were germinated at 27 C in the dark for various periods.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The senescence of cotyledons has also been studied (2,14,17,20,23 were soaked in tap water for 6 h. Following this, damaged and nonimbibed seeds were discarded. The remaining seeds were planted in horticultural grade Vermiculite and were germinated at 27 C in the dark for various periods.…”
Section: Introductionmentioning
confidence: 99%
“…The electron microscopy studies of Bain and Mercer (2) and of Solomos et al (20) have shown that there is deterioration in mitochondrial structure at later stages ofgermination. However, Solomos et al (20) isolated active mitochondria 14 days after the onset of imbibition, and Young et al (23) after 10 days. Also, Bain and Mercer (3) found that the young seedling was dependent on the cotyledons, even after the morphological characteristics of the young plant suggested otherwise.…”
mentioning
confidence: 99%
See 3 more Smart Citations